PENGARUH ECONOMIC VALUE ADDED (EVA), PROFITABILITAS DAN LEVERAGE TERHADAP RETURN SAHAM DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL INTERVENING (Studi Pada Sektor Industri Barang Konsumsi Yang Terdaftar Di Bei Periode 2013-2017) - Taslim, Fadli Ali; Suyadi, Nelly Anggriani (Jurnal MS, 2019)
This study aims to determine the effect of Economic Value Added (EVA), Profutability and Leverage on Stock Returns with Company Value as an Intervening Variable. In the consumer goods industry sector listed on the Indonesia Stock Exchange in 2013-2017. The results of this study indicate that the direct effect of economic value added (EVA) variables does not affect stock returns, profitability variables (ROE) do not affect stock returns, leverage variables (DER) do not affect stock returns and firm value variables (PBV) have no effect on stock returns. While the indirect effect of firm value (PBV) mediates the effect of economic value added (EVA) on stock returns, firm value (PBV) cannot mediate the effect of profitability (ROE) on stock returns and firm value (PBV) cannot mediate the effect of leverage (DER) ) of stock returns